IMPACT OF ACUTE TOXICITY OF LEAD ACETATE ON THE LEVEL OF ESSENTIAL TRACE METALS AND HISTOPATHOLOGICAL CHANGES IN CRUCIAN CARP. (CARASSIUS AURATUS GIBELIO) - S. A. Khan; X. Liu; B. R. Shah (Journal of Animal and Plant Sciences, 2014)
This study evaluated the acute toxicity effects of Pb2+ on essential trace metals behavior and histopathology of Crucian carp (Carassius auratus gibelio). The median lethal concentration (96 h LC50) of Pb2+ was determined to be 29.07 mgL-1 in a semi-static bioassay. The fish were exposed to sublethal concentration of 5mgL-1 as environmentally relevant Pb2+  for a period of 96 h.  Trace metals (Pb, Cu, Zn, Fe and Ca) levels were determined in the gill, liver, kidney and muscles tissue by ICP-OES. Regression analysis revealed that Pb2+ exposure had negative impact on the level of Cu, Zn, Fe and Ca in certain tissues (P<0.05;P<0.01). Histopathological changes in the gills of exposed fish were characterized by lamellar shrinkage, disruption of cartilaginous core, epithelial lifting, lamellar shortening with desquamation and curling of the secondary lamella. The trunk kidney had severe shrinkage of glomeruli, hypoplasia of hemopoietic tissue as well as mild glomerular and tubular necrosis. The liver showed cellular edema, necrosis of hepatocytes with nuclear degeneration and pyknotic nuclei.  The brain exhibited severe proliferation of glial cells, cellular necrosis, severe perivascular edema and satellitosis. These results clearly depict the deleterious effects of Pb2+ on trace metal metabolism and tissue  architecture of Crucain carp.
Keywords: Acute toxicity; 96 h LC50; environmentally relevant Pb2+; trace metals; histopathology